2017
DOI: 10.1080/20550324.2017.1325987
|View full text |Cite
|
Sign up to set email alerts
|

Application of surface-modified XLPE nanocomposites for electrical insulation- partial discharge and morphological study

Abstract: This paper investigates partial discharge (PD) characteristics of crosslinked polyethylene (XLPE) nanocomposites for unmodified, agglomerated, and Octylsilane-modified silica nanofillers (nano 1, 2, 3, 4, 5, 10 wt %) case. The surface modification of nanofiller helps to reduce the PD formation marginally. Octylsilane surface-modified XLPE/silica nano 3 wt % exhibits the lowest PD activity with highest discharge inception voltage and breakdown voltage. Also, the issue of change in the polymer structure due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…This includes the use of surfactants, which help to reduce high surface energy and interfacial tension in nanofillers . Improvement in dielectric properties such as AC and DC breakdown strength , electrical and water tree resistance as well as reduction in the space charge , partial discharge , permittivity and dielectric loss has been widely documented in nanocomposites with chemically treated nanoparticles.…”
Section: Application Of Micro and Nano‐size Filler In High Voltage Inmentioning
confidence: 99%
See 2 more Smart Citations
“…This includes the use of surfactants, which help to reduce high surface energy and interfacial tension in nanofillers . Improvement in dielectric properties such as AC and DC breakdown strength , electrical and water tree resistance as well as reduction in the space charge , partial discharge , permittivity and dielectric loss has been widely documented in nanocomposites with chemically treated nanoparticles.…”
Section: Application Of Micro and Nano‐size Filler In High Voltage Inmentioning
confidence: 99%
“…For example, Sharad and Kumar compared the theory of partial discharge propagation in XLPE nanocomposites filled with unmodified, agglomerated and octylsilane‐modified silica nanofillers (refer Fig. ).…”
Section: Application Of Micro and Nano‐size Filler In High Voltage Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Several models have been proposed in this regard . Sharad and Kumar reported that addition of modified nanofillers increased the chain mobility which leads to increased reactions at the interface . Moreover, the overlapping of neighboring interfaces could also substantially affect the properties of the composite .…”
Section: Introductionmentioning
confidence: 99%
“…It is universal to calculate the XLPE cable ampacity by the thermal-circuit method and simulation software, which follows the basic rule of calculating the maximum current through the conductor corresponding to the steady-state temperature of 90 • C in different environments [16]. The precondition of the cable ampacity calculation is setting the volumetric thermal capacity and thermal resistance of XLPE as fixed values [17][18][19]. To a large extent, these methods neglect the changes on XLPE insulation itself caused by the different aging factors and the influence of the heating and cooling process to the material during the cable operating condition, which would totally change the morphology of XLPE [20][21][22].…”
Section: Introductionmentioning
confidence: 99%